Australia's economic transition, unemployment, suicide and mental health needs. (February 2017) - Myles, Nicholas; Large, Matthew; Myles, Hannah; Adams, Robert; Liu, Dennis; Galletly, Cherrie
Objective: There have been substantial changes in workforce and employment patterns in Australia over the past 50 years as a result of economic globalisation. This has resulted in substantial reduction in employment in the manufacturing industry often with large-scale job losses in concentrated sectors and communities. Large-scale job loss events receive significant community attention. To what extent these mass unemployment events contribute to increased psychological distress, mental illness and suicide in affected individuals warrants further consideration. Methods: Here we undertake a narrative review of published job loss literature. We discuss the impact that large-scale job loss events in the manufacturing sector may have on population mental health, with particular reference to contemporary trends in the Australian economy. We also provide a commentary on the expected outcomes of future job loss events in this context and the implications for Australian public mental health care services. Results and conclusion: Job loss due to plant closure results in a doubling of psychological distress that peaks 9 months following the unemployment event. The link between job loss and increased rates of mental illness and suicide is less clear. The threat of impending job loss and the social context in which job loss occurs has a significant bearing on psychological outcomes. The implications for Australian public mental health services are discussed.